2022
DOI: 10.3389/fmicb.2022.1043414
|View full text |Cite
|
Sign up to set email alerts
|

Microbial diversity gradients in the geothermal mud volcano underlying the hypersaline Urania Basin

Abstract: Mud volcanoes transport deep fluidized sediment and their microbial communities and thus provide a window into the deep biosphere. However, mud volcanoes are commonly sampled at the surface and not probed at greater depths, with the consequence that their internal geochemistry and microbiology remain hidden from view. Urania Basin, a hypersaline seafloor basin in the Mediterranean, harbors a mud volcano that erupts fluidized mud into the brine. The vertical mud pipe was amenable to shipboard Niskin bottle and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 102 publications
0
1
0
Order By: Relevance
“…[19]. However, the results of this study showed that some vegetation can grow and develop around mud volcanoes.…”
contrasting
confidence: 53%
“…[19]. However, the results of this study showed that some vegetation can grow and develop around mud volcanoes.…”
contrasting
confidence: 53%
“…Particularly, the cryogenic, desiccating Martian conditions, along with the lack of metamorphic activity, might have contributed to biomarker longevity 124 . Corresponding terrestrial environments, which foster active ecosystems, are well-documented to maintain biomarker integrity over substantial geologic timescales 125 128 .…”
Section: Discussion On the Significance Of Amazonian Sedimentary Erup...mentioning
confidence: 99%
“…The distribution of the microbial communities in the deep sea is related to the sediment provenances. 26,27 Although classes Lokiarchaeia, Bathyarchaeia and Nitrososphaeria are common lineages in deep-sea sediments, 28 their varying abundances in different turbidite deposits along the JT (Figure 1B & C) indicate the difference in turbidite sources, 12,29 which is also suggested by the varying OC characteristics (Figure 2A). The abundance of the aerobic Candidatus Nitrosopumilus 30 in T1 and T3 turbidites of GeoB16431 (Figure 1B) indicates that these turbidites are composed of mostly remobilized oxic surficial sediments at the sea floor instead of deep subsurface sediments.…”
Section: Introductionmentioning
confidence: 99%